Association of Antibiotic Route and Outcomes in Children with Methicillin-Resistant Staphylococcus aureus Bacteremic Osteomyelitis - Jared Olson; Rana F. Hamdy; Alice J. Hsu; Pranita D. Tamma; Jeffrey S. Gerber; Nora F. Fino; Adam L. Hersh (Infectious Diseases and Therapy)
Abstract Introduction There remains uncertainty about whether transitioning to oral antibiotic therapy is appropriate for the management of children with methicillin-resistant Staphylococcus aureus (MRSA) bacteremic osteomyelitis. We compared clinical outcomes for children with MRSA osteomyelitis with associated bacteremia who were transitioned to discharge oral antibiotic therapy to those discharged on outpatient parenteral antibiotic therapy (OPAT). Methods We performed a retrospective, multicenter, cohort study of children ≤ 18 years hospitalized with MRSA bacteremic osteomyelitis across four children’s hospitals from 2007 to 2018 discharged on oral antibiotic therapy versus OPAT. The primary outcome was treatment failure within 6 months of discharge, defined as any of the following: diagnosis of chronic osteomyelitis, conversion from oral to IV antibiotic route, an operative procedure after the index hospitalization (abscess drainage, bone biopsy, arthrocentesis, or pathologic fracture) and/or recrudescence of MRSA bacteremia. Outcomes were analyzed in an inverse propensity score weighted (IPW) cohort. Results A total of 106 cases of MRSA bacteremic osteomyelitis were included; 44 (42%) were discharged in the oral antibiotic therapy group and 62 (59%) patients were discharged in the OPAT group. In the IPW cohort, treatment failure within 6 months of discharge occurred in 3.4% of children in the discharge oral therapy group and 16.3% in the OPAT group (P = 0.03). The odds of 6-month composite treatment failure between discharge oral therapy and OPAT were 0.18 (95% CI 0.05–0.61). Conclusions Discharge oral therapy was not associated with higher rates of treatment failure compared to OPAT for children with MRSA bacteremic osteomyelitis.